Detection of co-seismic earthquake gravity field signals using GRACE-like mission simulations. Issue 10 (15th May 2017) - Sharifi, Mohammad Ali; Shahamat, Abolfazl
Abstract: After launching the GRACE satellite mission in 2002, the earth's gravity field and its temporal variations are measured with a closer inspection. Although these variations are mainly because of the mass transfer of land water storage, they can also happen due to mass movements related to some natural phenomena including earthquakes, volcanic eruptions, melting of polar ice caps and glacial isostatic adjustment. Therefore this paper shows which parameters of an earthquake are more sensitive to GRACE-Like satellite missions. For this purpose, the parameters of the Maule earthquake that occurred in recent years and Alaska earthquake that occurred in 1964 have been chosen. Then we changed their several parameters to serve our purpose. The GRACE-Like sensitivity is observed by using the simulation of the earthquakes along with gravity changes they caused, as well as using dislocation theory under a half space earth. This observation affects the various faulting parameters which include fault length, width, depth and average slip. These changes were therefore evaluated and the result shows that the GRACE satellite missions tend to be more sensitive to Width among the Length and Width, the other parameter is Dip variations than other parameters. This article can be useful to the upcoming scenario designers and seismologists in their quest to study fault parameters.